Assessment Of Radioiodine Clearance In Differentiated Thyroid Cancer Patients In Hospital Kuala Lumpur - Rosdi, Abdullah Hanif (2018)
Radioiodine treatment has long been used since 1950’s for the treatment of various malignancy and non-malignancy diseases. It was the most popular, widely used, effective and safe unsealed source of radionuclide therapy. However, due to high gamma energy emitted from it which may induce stochastic effect to the public, radiation regulation has been introduced. Different countries have their own regulation regarding period of hospitalization needed before patient can be released to the public. Atomic Energy Licensing Act 1984 (Act 304) has stated that patient shall be discharged from isolation once the external dose rate falls below 50μSv/H which is equal to retained body activity of 1100MBq. To assess the appropriate isolation period of radioactive iodinated thyroid cancer patients in Hospital Kuala Lumpur.